2013
DOI: 10.1016/j.jacc.2013.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Higher Natriuretic Peptide Levels Associate With a Favorable Adipose Tissue Distribution Profile

Abstract: Objectives To investigate the association between natriuretic peptides and body fat distribution in a multiethnic cohort. Background Natriuretic peptides stimulate lipolysis, reduce weight gain, and promote adipocyte browning in animal models but data are lacking in humans. Methods 2619 participants without heart failure in the Dallas Heart Study underwent measurements of 1) B-type natriuretic peptide (BNP) and NT-proBNP and 2) body fat distribution by dual energy x-ray absorptiometry and magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 45 publications
5
81
1
3
Order By: Relevance
“…In a prospective study, low plasma levels of ANP were found to predict development of future diabetes, suggesting a causal role of ANP deficiency in diabetes development 103. In another study, higher NP levels were associated with a favorable body‐fat profile, including lower visceral fat and reduced insulin resistance 104. In a follow‐up study, higher NP levels were associated with reduced risk for diabetes 105…”
Section: Natriuretic Peptides In the Regulation Of Energy Metabolismmentioning
confidence: 99%
“…In a prospective study, low plasma levels of ANP were found to predict development of future diabetes, suggesting a causal role of ANP deficiency in diabetes development 103. In another study, higher NP levels were associated with a favorable body‐fat profile, including lower visceral fat and reduced insulin resistance 104. In a follow‐up study, higher NP levels were associated with reduced risk for diabetes 105…”
Section: Natriuretic Peptides In the Regulation Of Energy Metabolismmentioning
confidence: 99%
“…There also is evidence that a reduction in NP levels is associated to a less favorable adipose tissue distribution profile. Recent data from the Dallas Heart Study show that both BNP and NT-proBNP are inversely associated with visceral and liver fat and positively associated with lower glutofemoral body fat, independent of confounders including insulin resistance (53).…”
Section: Nps and Obesity Diabetes And Diabetes Complications Obesitymentioning
confidence: 99%
“…4 VAT is highly metabolically active and produces a variety of substances, for example interleukin-6 (IL-6), which contributes to low-grade inflammation and insulin resistance. 5,6 Furthermore, increased VAT has been associated with the activation of the sympathetic nervous system 7,8 and lower circulating concentrations of natriuretic peptides (NPs), 9,10 which could contribute to hypertension in individuals with increased VAT.…”
mentioning
confidence: 99%